Factors Influencing Entrepreneurship in Kamarian Village, Kairatu Subdistrict, SBB Regency - Tauran, Imanuela; Rehatta, Geradin; Sinay, Fransisca Riconita (Universitas Pattimura, 2024)
This research aims to investigate the factors influencing entrepreneurial interest in the community of Negeri Kamarian using a quantitative method and a positivistic approach. The study's population consists of entrepreneurs in the village, with a non-random sample of 40 individuals. The research variables include Self-Motivation (X1) and Family Environment (X2) as independent variables and Entrepreneurial Interest (Y) as the dependent variable, measured using a Likert scale. Primary data were collected through a closed questionnaire, followed by instrument validity and reliability tests. The results of the multiple regression analysis indicate that Self-Motivation significantly influences Entrepreneurial Interest, suggesting that the higher an individual's self-motivation, the greater their interest in entrepreneurship. On the other hand, the Family Environment does not significantly influence Entrepreneurial Interest. Nevertheless, simultaneously, Self-Motivation and the Family Environment jointly affect Entrepreneurial Interest with a significance level reaching 0.000.